ANALISIS PENILAIAN MAHASISWA TERHADAP TRANSISI STRATEGI PEMBELAJARAN DOSEN INSTITUT AGAMA ISLAM - Wahyuningrum, Sri Rizqi; Hasanah, Iswatun (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
In 2020, the world was shocked by the outbreak of a disease caused by corona virus. The regulations must be flexible according to the circumstances, this affects the student learning process in Islamic institute. Online learning methods return to offline methods. However, in practice, this situation requires lecturers to be more creative in conveying learning so that it is well received by students. The method of this research is the proportion analysis of the index scores survey results and descriptive statistics on the tangible aspect. There are 52% of students rate good on learning strategies of Islamic institute lecturers during the normal transition period. The result of the score index research is 84.13% (very good) for the interpretation of the score on the tangible aspect. It means that the tangible aspect of student assessment of the learning strategies of Islamic institute lecturers during the normal transition period is very good.